Preexisting Antibodies to an F(ab′)2 Antibody Therapeutic and Novel Method for Immunogenicity Assessment - Jane Ruppel; Ann Brady; Rebecca Elliott; Cecilia Leddy; Marco Palencia; Daniel Coleman; Jessica A. Couch; Eric Wakshull (Journal of Immunology Research)
Anti-therapeutic antibodies (ATAs) may impact drug exposure and activity and induce immune complex mediated toxicity; therefore the accurate measurement of ATA is important for the analysis of drug safety and efficacy. Preexisting ATAs to the hinge region of anti-Delta like ligand 4 (anti-DLL4) F(ab′)2, a potential antitumor therapeutic, were detected in cynomolgus monkey serum, which presented a challenge in developing assays for detecting treatment induced ATA. A total ATA assay was developed using a bridging ELISA that detected both anti-CDR and anti-framework ATA including anti-hinge reactivity. A competition assay that could detect 500 ng/mL of anti-CDR ATA in the presence of preexisting ATA was also developed to determine ATA specific to the anti-DLL4 F(ab′)2 CDR using anti-DLL4 F(ab′)2 and a control F(ab′)2. We used these assay methods in a cynomolgus monkey in vivo study to successfully evaluate total and anti-CDR ATA. The preexisting anti-hinge reactivity was also observed to a lesser extent in human serum, and a similar approach could be applied for specific immunogenicity assessment in clinical trials.